Oblique Corpectomy to Manage Cervical Myeloradiculopathy - Chibbaro Salvatore; Makiese Orphee; Bresson Damien; Reiss Alisha; Poczos Pavel; George Bernard (Neurology Research International)
Background. The authors describe a lateral approach to the cervical spine for the management of spondylotic myeloradiculopathy. The rationale for this approach and surgical technique are discussed, as well as the advantages, disadvantages, complications, and pitfalls based on the author's experience over the last two decades. Methods. Spondylotic myelo-radiculopathy may be treated via a lateral approach to the cervical spine when there is predominant anterior compression associated with either spine straightening or kyphosis, but without vertebral instability. Results. By using a lateral approach, the lateral aspect of the cervical spine and the vertebral artery are easily reached and visualized. Furthermore, the lateral part of the affected intervertebral disc(s), uncovertebral joint(s), vertebral body(ies), and posterior longitudinal ligament can be removed as needed to decompress nerve root(s) and/or the spinal cord. Conclusion. Multilevel cervical oblique corpectomy and/or lateral foraminotomy allow wide decompression of nervous structures, while maintaining optimal stability and physiological motion of the cervical spine.